Report of the 2019 NIST-FDA workshop on standards for next generation sequencing detection of viral adventitious agents in biologics and biomanufacturing. (March 2020) - Cleveland, Megan H.; Anekella, Bharathi; Brewer, Michael; Chin, Pei-Ju; Couch, Heather; Delwart, Eric; Huggett, Jim; Jackson, Scott; Martin, Javier; Monpoeho, Serge; Morrison, Tom; Ng, Siemon H.S.; et al.
Abstract: Adventitious virus testing assures product safety by demonstrating the absence of viruses that could be unintentionally introduced during the manufacturing process. The capabilities of next-generation sequencing (NGS) for broad virus detection in biologics have been demonstrated by the detection of known and novel viruses that were previously missed using the recommended routine assays for adventitious agent testing. A meeting was co-organized by the National Institute of Standards and Technology and the U.S. Food and Drug Administration on September 18–19, 2019 in Gaithersburg, Maryland, USA, to facilitate standardization of NGS technologies for applications of adventitious virus testing in biologics. The goal was to assess the currently used standards for virus detection by NGS and their public availability, and to identify additional needs for different types of reference materials and standards (natural and synthetic). The meeting focused on the NGS processes from sample preparation through sequencing but did not thoroughly cover bioinformatics, since this was considered to be the topic of a separate meeting. Highlights: The goal of the NIST-FDA workshop was NGs standardization for applications of adventitious virus testing in biologics. The aim was to identify additional needs for different types of reference materials and standards (natural and synthetic). Whole virus preparations and extracted nucleic acids can be used to evaluate different steps in the NGS workflow. All types of viral genomes should be represented. Different kinds of standards for "method development" and "method validation" were discussed.